Salivary levels of inflammatory and anti-inflammatory biomarkers in periodontitis patients with and without acute myocardial infarction: implications for cardiovascular risk assessment - Sudhir Varma; Biju Thomas; Biju Thomas; K. Subrahmanyam; K. Subrahmanyam; Kimberly Duarte; Kimberly Duarte; Mohammed A. Alsaegh; Divya Gopinath; Sam T. Kuriadom; Jayaraj Narayanan; Vijay B. Desai; et al. (Frontiers Media S.A., 2024)
BackgroundPeriodontitis is initiated by a dysbiotic activity and furthermore leads to a chronic inflammatory response. The presence of pro-inflammatory markers plays an important role in the inflammatory load. Macrophage inflammatory protein-1 alpha (MIP-1α) and C-reactive protein (CRP) are pro- inflammatory biomarkers that quantify clinical and subclinical inflammation in cardiac ischemia in cardiac inflammation and disease. Adiponectin is an anti-inflammatory marker associated with good health. The susceptibility of periodontitis patients to cardiovascular events needs to be evaluated.ObjectiveThis study aims to assess the levels of biomarkers in periodontitis patients with and without acute myocardial infarction (AMI) compared to controls.Material and methodsPro-inflammatory and anti-inflammatory analytes were examined by collecting unstimulated saliva from three groups (n = 20/each): healthy individuals, individuals with stage III periodontitis, and post-myocardial infarction patients with stage III periodontitis. The samples were collected within 48 h of AMI.ResultsAdiponectin levels were significantly lower in patients with periodontitis with and without AMI compared to controls, while CRP and MIP-1α were significantly higher in patients with periodontitis with and without AMI compared to controls. The highest titers for MIP-1α and CRP were detected among patients with periodontitis with and AMI.ConclusionOur study provides possible evidence of the association between periodontitis and salivary analytes that occur in tandem with cardiovascular disease. The lower levels of Adiponectin and higher levels of CRP and MIP-1α in patients with periodontitis indicate that this condition is a potential risk factor for cardiovascular disease. The findings emphasize the importance of early detection and intervention for periodontitis patients to prevent cardiovascular events.